Distribution of the myelin-associated glycoprotein and P0 protein during myelin compaction in quaking mouse peripheral nerve (The Rockefeller University Press, 1988)
Ultrastructural studies have shown that during early stages of Schwann cell myelination mesaxon membranes are converted to compact myelin lamellae. The distinct changes that occur in the spacing of these Schwann cell membranes are likely to be mediated by the redistribution of (a) the myelin-associated glycoprotein, a major structural protein of mesaxon membranes; and (b) P0 protein, the major structural protein of compact myelin. To test this hypothesis, the immunocytochemical distribution of these two proteins was determined in serial 1-micron- thick Epon sections of ventral roots from quaking mice and compared to the ultrastructure of identical areas in an adjacent thin section. Ventral roots of this hypomyelinating mouse mutant were studied because many fibers have a deficit in converting mesaxon membranes to compact myelin. The results indicated that conversion of mesaxon membranes to compact myelin involves the insertion of P0 protein into and the removal of the myelin-associated glycoprotein from mesaxon membranes. The failure of some quaking mouse Schwann cells to form compact myelin appears to result from an inability to remove the myelin-associated glycoprotein from their mesaxon membranes.